Column bioleaching copper and its kinetics of waste printed circuit boards (WPCBs) by Acidithiobacillus ferrooxidans. (December 2015) - Chen, Shu; Yang, Yuankun; Liu, Congqiang; Dong, Faqin; Liu, Bijun
Highlights: Column bioleaching of waste printed circuit boards by Acidithiobacillus ferrooxidans was examined. The kinetic process was fitted using conventional kinetic models and modified kinetic models. The column bioleaching of rate was controlled by the diffusion of ions through the liquid boundary layer. Abstract: Application of bioleaching process for metal recovery from electronic waste has received an increasing attention in recent years. In this work, a column bioleaching of copper from waste printed circuit boards (WPCBs) by Acidithiobacillus ferrooxidans has been investigated. After column bioleaching for 28 d, the copper recovery reached at 94.8% from the starting materials contained 24.8% copper. Additionally, the concentration of Fe 3+ concentration varied significantly during bioleaching, which inevitably will influence the Cu oxidation, thus bioleaching process. Thus the variation in Fe 3+ concentration should be taken into consideration in the conventional kinetic models of bioleaching process. Experimental results show that the rate of copper dissolution is controlled by external diffusion rather than internal one because of the iron hydrolysis and formation of jarosite precipitates at the surface of the material. The kinetics of column bioleaching WPCBs remains unchanged because the size and morphology of precipitates are unaffected by maintaining the pH of solution at 2.25 level. In bioleaching process, the formation of jarosite precipitate can be prevented by adding dilute sulfuric acid and maintaining an acidic condition of the leaching medium. In such way, the Fe 2 + –Fe 3+ cycle process can kept going and create a favorable condition for Cu bioleaching. Our experimental results show that column Cu bioleaching from WPCBs by A. ferrooxidans is promising.